Sirtuin 1 modulation in rat model of acetaminophen-induced hepatotoxicity - Wojnarová, L; Kutinová Canová, N; Farghali, H; Kučera, T (Physiological research, 2015)
Sirtuin 1 (SIRT1) is involved in important biological processes such as energy metabolism and regulatory functions of the cell cycle, apoptosis, and inflammation. Our previous studies have shown hepatoprotective effect of polyphenolic compound resveratrol, which is also an activator of SIRT1. Therefore, the aim of our present study was to clarify the role of SIRT1 in process of hepatoprotection in animal model of drug-induced liver damage. Male Wistar rats were used for both in vivo and in vitro studies. Hepatotoxicity was induced by single dose of acetaminophen (APAP). Some rats and hepatocytes were treated by resveratrol or synthetic selective activator of sirtuin 1 (CAY10591). The degree of hepatotoxicity, the activity and expression of the SIRT1 were determined by biochemical, histological and molecular-biological assessments of gained samples (plasma, liver tissue, culture media and hepatocytes). Resveratrol and CAY attenuated APAP-induced hepatotoxicity in vivo and in vitro. Moreover, both drugs enhanced APAP-reduced SIRT1 activity. Our results show that modulation of the SIRT1 activity plays a role in hepatoprotection. Synthetic activators of SIRT1 would help in understanding the role of SIRT1 and are therefore a major boost towards the search for specific treatment of liver disease.
Keywords: Acetaminophen; Cell Survival; Sirtuin 1; Resveratrol; resveratrol; lékové postižení jater; stilbeny; paracetamol; krysa rodu Rattus; zvířata; Cells, Cultured; potkani Wistar; Rats, Wistar; Stilbenes; Male; Chemical and Drug Induced Liver Injury; kultivované buňky; Rats; Hepatocytes; Animals; mužské pohlaví; sirtuin 1; hepatocyty; Disease Models, Animal; viabilita buněk; modely nemocí na zvířatech